Geographical identification of sites of historical and archaeological interest using cartographic techniques - Mollo, Norberto Mollo (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2022)
The old cartography in the Pampas area, basically constituted by geographical maps of a military nature from the 19th century and the survey plans drawn up by the first surveyors, constitutes a profuse source of data about the location of place names of indigenous origin. On the other hand, a careful reading of the diaries of the military expeditions carried out in 1879 reveals the presence of numerous rankülche toponyms not recorded in the first measurements. It also reveals the existence of historical errors in the location of certain places, which are maintained to the present, as is the case of Poitahué. Simultaneous work with old maps, survey charts, cartography from the IGN (National Geographic Institute), satellite images and travel diaries of the soldiers who made up the expeditionary column commanded by Colonel Eduardo Racedo, allow a good approximation to elucidate the location of several places of historical and archaeological interest. Some of these places had been wrongly mapped and others were not on any map. An exhaustive etymological analysis is carried out for each place name, taking into account the existence of the root, its semantic suitability, documentary compatibility, linguistic viability and also an observation of the place to determine if the root or etym responds to any current or past characteristic. . The rescue of this rankülche toponymic corpus and its location may be important to clarify historical and geographical aspects of this ethnic group, which may contribute to expanding their ancestral knowledge and promoting the strengthening of their identity.